Stroop theory, memory, and prefrontal cortical functioning: reply to Cohen et al. (1997) - Schooler, Carmi; Neumann, Ewald; Caplan, Leslie J. (Journal of Experimental Psychology. General, 1997)
In this article, the authors respond to J. D. Cohen, K. O. Dunbar, D. M. Barch and T. S. Braver's (1997) comment on their target article. The present article (a) takes issue with the characterization given by Cohen et al. of the authors' approach as a classical speed-of-processing account of Stroop effects, (b) discusses the value and relevance of other theoretical concepts, such as traditional accounts of working memory and parallel distributed processing (PDP) approaches to Stroop effects, (c) further examines the possibility that the differences the authors observed in Experiment 2 between normal participants' performance and that of participants with schizophrenia may have been due to distractor stimulus degradation, particularly for participants with schizophrenia, and (d) argues for the relevance of the prefrontal cortex, as well as other brain areas, in accounting for their results. The authors conclude with a final theoretical question. Reprinted by permission of the publisher.